Investigation of optical and electrical properties of multilayer thin films of ZnTe/CdSe - P. Ansari, R. A. Dar and Y. C. Sharma (International Journal of Advanced Science and Technology, 2020)
Zinc Telluride (ZnTe) and Cadmium Selenide (CdSe) are II-VI semiconductors having bandgap of 2.27eV and 1.74eV. In this work multilayers of ZnTe/CdSe thin films have been prepared by e-beam evaporation, having thickness 50nm/50nm i.e. (100nm) to 100nm/100nm i.e. (200nm); optical bandgap and absorbance were studied by UV-VIS spectrophotometer in the wavelength range 200nm-1000nm. The bandgap result showed that the films have semiconducting nature. Electrical properties of the films have been studied by I-V characteristics and Hall measurement technique.